No Wound Healing Complications or Recurrences Were Seen and a High Level of Satisfaction Was Reported in Patients Who Underwent Endoscopic Olecranon Bursectomy for Recalcitrant Olecranon Bursitis - Jeffrey R. Simpson, M.S; Austin Fagerberg, M.S; Robert Toledo, M.D; Patrick W. Joyner, M.D (Elsevier, 2024)
Purpose: To determine the outcomes of endoscopic olecranon bursectomy for the treatment of recalcitrant olecranon bursitis in one surgeon's practice. Methods: A retrospective analysis was conducted on all patients who underwent an endoscopic olecranon bursectomy for the treatment of recalcitrant olecranon bursitis between January 2018 and May 2021 at one surgeon's practice. Demographic variables as well as causes for olecranon bursitis such as aseptic, septic, and gouty tophi were recorded. In addition, any complications such as infection, recurrence, wound failure, or hospitalizations were documented, with wound dehiscence, recurrence of bursitis, and return to the operating room being the primary outcome measures. During the final phone encounter before finalizing this project, patients were queried to obtain the patient-reported form of the American Shoulder and Elbow Surgeons Elbow Questionnaire, quick Disabilities of the Arm Shoulder and Hand score, and the Single Assessment Numeric Evaluation score. Results: Our study included 28 patients (23 male and 5 female) with an average age of 68 years (ranging from 33-86 years), all of whom had follow-up. The average follow-up was 24.7 months (range 3-42 months). There were 15 cases (54%) of aseptic bursitis, 13 cases (46%) of septic bursitis, and 7 cases (25%) that contained gouty tophi (5 aseptic and 2 septic). Of the 28 patients, 4 experienced complications. These all occurred within 3 months of surgery. One necessitated hospitalization and intravenous antibiotics, 2 were minor infections treated with oral antibiotics, and one was swelling treated successfully with in-office aspiration. Overall, 24 (86%) patients reported no issues at all related to the surgery. There were no instances of recurrence, wound failure, or secondary operations. Of the 20 (71.4%) patients who were reached for patient-reported form of the American Shoulder and Elbow Surgeons Elbow Questionnaire, quick Disabilities of the Arm Shoulder and Hand score, and Single Assessment Numeric Evaluation scores, all 20 patients reported no residual pain or difficulties with daily tasks. Average satisfaction with the procedure was 9.9 of 10 and, on average, patients reported that their elbow functionality was 96% with 100% representing completely normal. Conclusions: In this population, patients who underwent endoscopic olecranon bursectomy experienced no recurrences or wound-healing complications necessitating return to the operating room. In addition, patients reported high function and satisfaction after the procedure. Level of Evidence: Level IV, therapeutic case series.